3 axis CNC machine controllers - Mohd Azri, Abdul Rahman (2013)
This study focuses on the programming of 3 Axis CNC machines where user can key in the data through Visual Basic software and as the results, CNC 3 axis machine will move according to the user data input. These project required 3 stepper motor as the motor is use to move the machine into X, Y and Z directions. The motor then will connect to the output of Darlington IC (ULN2803A). The inputs of Darlington IC are connecting to the parallel port that will connect to the computer. The Darlington IC also known as controller of this project. The most important part in this project is the programming. The movement is control by the program that will be written on C programming that was built in Visual Basic software. This program will determine how many rotation that the motor will rotate as the rotating motor will cause the distance of the machine move according to its axis. The programs also will activate the address on the parallel port so that parallel port will send the signals to the input controller. As a results, the motor will move and the machine also will go to its locations depends on the user data input on the Visual Basic. This proposal includes the introduction of the project, literature review and research methodology for further planning of investigation.